Adaptive regulation or governmentality: patient safety and the changing regulation of medicine - Waring, J
Studies from across the world have shown that clinical mistakes are a major threat to the safety of patient care (World Health Organisation 2004). For the National Health Service (NHS) of England and Wales it is estimated that one in ten hospital patients experience some form of error, and each year these cost the service over £2billion in remedial care (Department of Health 2000). Unsurprisingly, ‘patient safety’ is now a major international health policy priority, questioning the efficacy of existing regulatory practices and proposing a new ethos of learning. Within England and Wales, the National Patient Safety Agency (NPSA) has been created to lead policy development and champion service-wide learning, whilst throughout the NHS the National Reporting and Learning System (NRLS) has been introduced to enable this learning (NPSA 2003). This paper investigates the extent to which, in seeking to better manage the threats to patient safety, this policy agenda represents a transition in medical regulation.